2006
DOI: 10.1007/s11255-006-9014-8
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Polycythaemia Associated with Unilateral Renal Cystic Disease

Abstract: Unilateral renal cystic disease (URCD) is a rare condition, with pathological features indistinguishable from autosomal dominant polycystic kidney disease (ADPKD). In contrast to this condition, however, URCD is not inherited, is not associated with progressive deterioration in renal function, and is unilateral. We present a case of URCD associated with polycythaemia, which showed resolution following nephrectomy. Secondary polycythaemia has not previously been reported in cases of URCD, but may be hypothesise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…Arterial oxygen level or oxygen saturation should be normal, excluding hypoxia-driven erythrocytosis. An uncommon, but important etiology of post-transplantation erythrocytosis is renal cell carcinoma affecting the native kidney(s), especially if acquired cystic disease is present and results from constitutive erythropoietin release by carcinoma cells or renal cysts [12,13]. Ureteral stenosis and hydronephrosis may cause erythrocytosis on occasion [13].…”
Section: Post-transplant Erythrocytosismentioning
confidence: 99%
“…Arterial oxygen level or oxygen saturation should be normal, excluding hypoxia-driven erythrocytosis. An uncommon, but important etiology of post-transplantation erythrocytosis is renal cell carcinoma affecting the native kidney(s), especially if acquired cystic disease is present and results from constitutive erythropoietin release by carcinoma cells or renal cysts [12,13]. Ureteral stenosis and hydronephrosis may cause erythrocytosis on occasion [13].…”
Section: Post-transplant Erythrocytosismentioning
confidence: 99%
“…It is not known whether SRC also may produce EPO. Attar et al [6] showed that patients with unilateral cystic disease as well as patients with ADPKD may have polycythemia. HCT, RBC, and HGB may serve as indirect equivalents of plasma EPO concentration.…”
Section: Discussionmentioning
confidence: 99%
“…However, there might be other indications. It was shown that polycythemia may occur in patients with unilateral cystic disease [6], probably due to production of erythropoietin (EPO) by the cyst wall. This phenomenon was first described in acquired dominant polycystic kidney disease (ADPKD) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…38 Burk at al. Erythrocytosis has also been described in cases of tumors arising in polycystic kidneys 40 and renal cysts, 41 as well as in parathyroid adenoma, 42 pheochromocytoma, 43 hepatocellular adenoma 44 and carcinoma, 45 cerebellar hemangioblastoma 46 and meningiomas. The increase in RCM was associated with an elevation in erythropoietic stimulatory activity in serum, pleural fluid and tumor-cyst fluid supporting the presence of autonomous tumor secretion of Epo or an Epo-like substance.…”
Section: Laboratory Featuresmentioning
confidence: 99%